2009
DOI: 10.1074/jbc.m805593200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Serine 271 on 5-Lipoxygenase and Its Role in Nuclear Export

Abstract: The enzyme 5-lipoxygenase (5-LO) initiates the biosynthesis of leukotrienes, inflammatory mediators involved in immune diseases and defense. The subcellular localization of 5-LO is regulated, with nuclear import commonly leading to increased leukotriene production. We report here that 5-LO is constitutively phosphorylated on Ser-271 in transfected NIH 3T3 cells. This residue is nested in a classical nuclear export sequence, and phosphorylated Ser-271 5-LO was exclusively found in the nucleus by immunofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…Detection limits of the corresponding phosphopeptides have been determined and tagged 5-LO isolated from MM6 cells was shown to be phosphorylated on Ser271, regardless of the cell treatment. This is in accordance with findings from another group showing that 5-LO is constitutively phosphorylated at Ser271 in transfected NIH 3T3 cells [31].…”
Section: Discussionsupporting
confidence: 93%
“…Detection limits of the corresponding phosphopeptides have been determined and tagged 5-LO isolated from MM6 cells was shown to be phosphorylated on Ser271, regardless of the cell treatment. This is in accordance with findings from another group showing that 5-LO is constitutively phosphorylated at Ser271 in transfected NIH 3T3 cells [31].…”
Section: Discussionsupporting
confidence: 93%
“…In this study we confirmed previously obtained results by us and others that indicate changes in expression and sub-cellular location of 5-and 12-LOX enzymes in relation to the progression of the cell cycle [36]. The pure compound PA, isolated from the traditional medicinal herb Iceland moss, inhibits 5-and 12-LOX [23,27] and has anti-proliferative effects on various cancer cell lines [26].…”
Section: Discussionsupporting
confidence: 91%
“…One mechanism of control of 5-LOX location is phosphorylation. For instance, phosphorylation of Ser-271 interferes with the export of 5-LOX from the nucleus (44). Thus, cell stimulation results in the Ca 2ϩ -dependent targeting of 5-LOX to the inner and/or outer nuclear membrane(s), depending upon the compartment(s) in which the unstimulated enzyme resides.…”
Section: Compartmentalizationmentioning
confidence: 99%